Practical True Random Number Generator Using CMOS Image Sensor Dark Noise - Byung Kwon Park; Hojoong Park; Yong-Su Kim; Ju-Sung Kang; Yongjin Yeom; Changhui Ye; Sung Moon; Sang-Wook Han (IEEE Access, 2019)
We present a true random number generator (TRNG) using dark noise of a CMOS image sensor. Because the proposed TRNG is based on the dark characteristics of the CMOS image sensor, it does not require any additional hardware, such as light source and optics, for providing true randomness. Therefore, it can be a promising solution for compact and low-cost mobile application. By using NIST SP 800-90B entropy assessment suite, we evaluate the min-entropy for the raw outputs of our original noise source and the final random numbers including post-processing as well. We also adopt NIST SP 800-22 statistical randomness test suite for the evaluation of the random numbers. The test results demonstrate that the generated random numbers pass all the statistical tests and have high entropy.